2016
DOI: 10.1007/s13577-016-0148-4
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-124 upregulation inhibits proliferation and invasion of osteosarcoma cells by targeting sphingosine kinase 1

Abstract: Increasing evidence has confirmed that the dysregulation of microRNAs (miRNAs) contributes to the proliferation and invasion of human cancers. Previous studies have shown that the dysregulation of miR-124 is in numerous cancers. However, the roles of miR-124 in human osteosarcoma (OS) have not been well clarified. Therefore, this study was to investigate the biological functions and molecular mechanisms of miR-124 in OS cell lines, discussing whether it could be a therapeutic biomarker of OS in the future. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Several lines of evidence have also demonstrated that Sphk1 is a downstream target of microRNAs and acts as oncogene in promoting tumorigenesis and progression. For example, miRNA-124 has been shown downregulated in various types of solid cancers, and acts as a tumor suppressor by inhibiting cancer cell proliferation, invasion, and metastasis in the head and neck squamous cell carcinoma, osteosarcoma, ovarian, and gastric cancers by targeting Sphk1 signaling [ 27 , 28 , 29 ]. MiRNA-101 inhibited colorectal cancer cell proliferation by targeting Sphk1 [ 30 ].…”
Section: Sphk1/s1p Signaling In Cell Growth Cell Cycle and Tumormentioning
confidence: 99%
“…Several lines of evidence have also demonstrated that Sphk1 is a downstream target of microRNAs and acts as oncogene in promoting tumorigenesis and progression. For example, miRNA-124 has been shown downregulated in various types of solid cancers, and acts as a tumor suppressor by inhibiting cancer cell proliferation, invasion, and metastasis in the head and neck squamous cell carcinoma, osteosarcoma, ovarian, and gastric cancers by targeting Sphk1 signaling [ 27 , 28 , 29 ]. MiRNA-101 inhibited colorectal cancer cell proliferation by targeting Sphk1 [ 30 ].…”
Section: Sphk1/s1p Signaling In Cell Growth Cell Cycle and Tumormentioning
confidence: 99%
“…The study of drugs affects the expression level of miRNAs in OS cells, which in turn affects the progression and prognosis of tumors, and provides a new direction for the study of molecular targeted drugs for the treatment of OS [43][44][45][46]. However, although there is a deep understanding of the differential expression and functional roles of some miRNAs in OS, there are still many difficulties to overcome in order to treat OS through the targeting of miRNAs: the sequence error of the miRNA sequence library, poor RNA extraction methods, variability in detection and analysis, diversity of bioinformatics analysis, and non-standardization of miRNA clinical tests [47,48]. In conclusion, the exploration of the relationship between miRNAs and OS provides new ideas and challenges for the early diagnosis, molecular targeted therapy, and prognosis of OS [49][50][51].…”
Section: Resultsmentioning
confidence: 99%
“…Their study demonstrated that overexpression of miR-409-3p reduced OS cell migration and invasion and that this effect was mediated by targeting catenin-δ1, which has been described as an oncogene via aberrant regulation of Rho GTPases and the transcriptional activation of other oncogenes [ 235 ]. Within the last year, two groups have studied miR-124 in OS [ 236 , 237 ]; the first demonstrated that upregulation of miR-124, which is often downregulated in OS cells, blocks proliferation and invasion by targeting the SPHK1 gene. SPHK1 has been reported to be involved in several cellular processes including cancer metastasis.…”
Section: Mirnas and Primary Bone Tumoursmentioning
confidence: 99%
“…SPHK1 has been reported to be involved in several cellular processes including cancer metastasis. Hence, Zhou et al have described for the first time an association between miR-124 and SPHK1 [ 236 ]. The other group showed the tumour suppressor activity of miR124 and demonstrated that this activity is related to targeting B7-H3, a protein that promotes uncontrollable proliferation and invasion [ 237 ].…”
Section: Mirnas and Primary Bone Tumoursmentioning
confidence: 99%